Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3844/ajavsp.2020.284.290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotic Feed Additives on Honeybee Colonies Overwintering

Abstract: The paper presents the study on the effect of two types of probiotic feed additives of different composition on the quality of honeybee colonies during wintering. Feed additive called SpasiPchel contains 2 strains of bacteria Bacillus subtilis anfeed additive PcheloNormosil contains Lactobacillus and Bifidobacterium strains and arabinogalactan (prebiotic isolated from Siberian larch needles). If honeybees received Spasipchel and Pchelonormosil during the feeding in cages their lifespan increased. Honeybee colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…The data obtained by us on the effect of stimulating fertilizing on the x functional activity of queen bees are consistent with the materials of a number of domestic and foreign researchers [11][12][13][14][15][16]. Scaling up the results of apiary research in the future opens up new opportunities for strengthening the immunity of bees, reducing the effects of adverse environmental factors, increasing the yield of marketable products and the transition of this industry to an ecological path of development.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The data obtained by us on the effect of stimulating fertilizing on the x functional activity of queen bees are consistent with the materials of a number of domestic and foreign researchers [11][12][13][14][15][16]. Scaling up the results of apiary research in the future opens up new opportunities for strengthening the immunity of bees, reducing the effects of adverse environmental factors, increasing the yield of marketable products and the transition of this industry to an ecological path of development.…”
Section: Discussionsupporting
confidence: 86%
“…The presented facts lead to a gradual reduction in the global population of subspecies (Apis mellifera mellifera, Apis mellifera carpatica, Apis mellifera ligustica etc.) of the honey bee, and this, in turn, leads to a decrease in the numerical and species composition of agricultural and wild flora in countries and states [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that some commercial probiotics for animals and humans have demonstrated beneficial effects on tested honey bees ( Kaznowskia et al 2005 , Mishukovskaya et al 2020 ), while others, even hbs-LAB, have been reported to increase pathogen susceptibility ( Schmidt and Engel 2016 ) and bee mortality ( Borges et al 2021 ), and fail to reduce background loads of P . larvae spore in honey bee colonies ( Lamei et al 2020 ).…”
Section: Limits About the Current Application Of Probiotics In Afb Co...mentioning
confidence: 99%
“…Mishukovskaya G. та ін. досліджували вплив двох типів пробіотичних кормових добавок різного складу на якісні показники зимівлі бджіл (Mishukovskaya et al, 2020). Ними встановлено, що використання восени SpasiPchel та PcheloNormosil сприяло кращій підготовці бджіл до зимівлі, підвищувалися ступінь розвитку жирового тіла та тривалість життя бджіл і відповідно зростала кількість вирощеного розплоду навесні.…”
Section: вісник сумського національного аграрного університетуunclassified